Pulp and paper chemistry and technology. Volume 4, - Ek, Monica; Gellerstedt, Göran; Henriksson, Gunnar (Pulp and Paper Chemistry and Technology ;, 2009)
The production of forestry products is based on a complex chain of knowledge in which the biological material wood with all its natural variability is converted into a variety of fiber-based products, each one with its detailed and specific quality requirements. This four volume set covers the entire spectrum of pulp and paper chemistry and technology from starting material to processes and products including market demands. Supported by a grant from the Ljungberg Foundation, the Editors at the Royal Institute of Technology, Stockholm, Sweden coordinated over 30 authors from university and ind.